Klimatanpassning i en historisk kontext- En studie om den västsvenska landsbygdens klimatanpassning och utveckling under 1800-talet. - Häggander,Wilhelm (2015)
In Sweden there are many people who take the food on our tables for granted, there is rarely anyone who reflects on the fact that it was hard work behind. The situation has not always been like that. During the late 1800s there were still many people living in rural areas and their livelihood was farming. Their jobs and mundane chore was to produce, if not the whole, but parts of the food that would later be consumed in the household. The studied period in this paper was colder than today, and people therefore had to adapt to this. The study's purpose is therefore to examine how society could adapt to the current climate. The study is therefore based on material from Statistics Sweden but also historical meteorological data from SMHI. This study shows how the western Swedish farmers changed their way of farming. This was done by the previous land consolidation reforms made possible a more large-scale agriculture and individual responsibility had to be higher. A colder climates generally generated smaller harvests, but when agricultural society had undergone major change through land parcelling and new technological innovations had entered the market as farmers were able to maintain production even in years with low average temperatures. The study also shows how farmers came to have more animals on farms, to produce both meat and dairy products. Farmers also came to increase potato cultivation which gave large harvests and gave a more differentiated work and facilitated the work of sowing and harvesting. The study also shows that growing oats was an important crop to grow as it not only could be consumed by the farmer himself but it was also important as animal feed. However, it can be difficult to draw general conclusions over larger areas where the geographical area is important for people. Since Sweden is long and narrow, there are natural differences between north and south.
Keywords: grain growing; farmers; potato; West Sweden; animal housekeeping; Climate adaptation